Prognostic value of FOXP3+ regulatory T cells in patients with diffuse large B-cell lymphoma: a systematic review and meta-analysis - Jing Yang; Min Zhang; Kehu Yang; Qianqian Liu; Liyan Zhang; Yuping Bai; Tingting He; Ziru Zhao (BMJ Open, 2022)
Objectives We aimed to comprehensively evaluate the relationship between forkhead box P3 (FOXP3+) regulatory T cell (Treg) expression and diffuse large B-cell lymphoma (DLBCL) prognosis and to explore the sources of heterogeneity of the results.Design Systematic review and meta-analysis.Data sources We searched the Cochrane Library, PubMed, Embase and Web of Science databases up to 5 December 2021.Eligibility criteria We included studies that analysed the prognostic significance of FOXP3+ Tregs in DLBCL. We included studies reported in Chinese or English that reported HRs and related 95% CIs for prognosis.Data extraction and synthesis We extracted data from eligible studies. HRs and 95% CIs were used to assess the prognostic value.Results Fourteen eligible studies were identified. FOXP3+ Treg expression was not associated with overall survival (OS) (HR=0.72, 95% CI 0.45 to 1.16) or progression-free survival (HR=0.86, 95% CI 0.54 to 1.38). The three approaches used to measure FOXP3+ Treg expression (pinteraction<0.001) may be the source of the heterogeneity of the results. Subgroup analysis found that a higher expression of FOXP3+ Tregs was associated with better OS in all populations and in Asians when FOXP3+ Treg expression was measured by the number of positive cells (HR=0.36 (95% CI 0.22 to 0.58) in the former, HR=0.33 (95% CI 0.20 to 0.55) in the latter) or the percentage of positive cells (HR=0.49 (95% CI 0.27 to 0.89) in the former, HR=0.38 (95% CI 0.21 to 0.70) in the latter). However, when measured by the score, inverse results were found (HR=1.56, 95% CI 1.01 to 2.42).Conclusions Approaches to measuring FOXP3+ Treg expression might be the major source of heterogeneity in studies of the prognostic significance of FOXP3+ Tregs in DLBCL. FOXP3+ Treg expression might be used to predict the prognosis of patients with DLBCL when FOXP3+ Treg expression is calculated by the number or the percentage of positive cells, especially in Asian populations.